The kinesin motor KIF1C is a putative transporter of the exon junction complex in neuronal cells - Nagel, Maike; Noß, Marvin; Xu, Jishu; Horn, Nicola; Ueffing, Marius; Boldt, Karsten; Schüle-Freyer, Rebecca (RNA, 2023)
Neurons critically depend on regulated RNA localization and tight control of spatiotemporal gene expression to maintain their morphological and functional integrity. Mutations in the kinesin motor protein gene KIF1C cause hereditary spastic paraplegia, an autosomal recessive disease leading to predominant degeneration of the long axons of central motoneurons. In this study, we aimed to gain insight into the molecular function of KIF1C and understand how KIF1C dysfunction contributes to motoneuron degeneration. We used affinity proteomics in neuronally differentiated neuroblastoma cells (SH-SY5Y) to identify the protein complex associated with KIF1C in neuronal cells; candidate interactions were then validated by immunoprecipitation, and mislocalization of putative KIF1C cargoes was studied by immunostainings. We found KIF1C to interact with all core components of the exon junction complex (EJC); expression of mutant KIF1C in neuronal cells leads to loss of the typical localization distally in neurites. Instead, EJC core components accumulate in the pericentrosomal region, here colocalizing with mutant KIF1C. These findings suggest KIF1C as a neuronal transporter of the EJC. Interestingly, the binding of KIF1C to the EJC is RNA-mediated, as treatment with RNase prior to immunoprecipitation almost completely abolishes the interaction. Silica-based solid-phase extraction of UV-cross-linked RNA-protein complexes furthermore supports direct interaction of KIF1C with RNA, as recently also demonstrated for kinesin heavy chain. Taken together, our findings are consistent with a model where KIF1C transports mRNA in an EJC-bound and therefore transcriptionally silenced state along neurites, thus providing the missing link between the EJC and mRNA localization in neurons.